Amyloid accumulation in Down syndrome measured with amyloid load. Issue 1 (16th April 2020) - Zammit, Matthew D.; Laymon, Charles M.; Betthauser, Tobey J.; Cody, Karly A.; Tudorascu, Dana L.; Minhas, Davneet S.; Sabbagh, Marwan N.; Johnson, Sterling C.; Zaman, Shahid H.; Mathis, Chester A.; Klunk, William E.; Handen, Benjamin L.; et al.
Abstract: Introduction: Individuals with Down syndrome (DS) show enhanced amyloid beta (Aβ) deposition in the brain. A new positron emission tomography (PET) index of amyloid load ( AβL ) was recently developed as an alternative to standardized uptake value ratios (SUVrs) to quantify Aβ burden with high sensitivity for detecting and tracking Aβ change. 1 Methods: AβL was calculated in a DS cohort (N = 169, mean age ± SD = 39.6 ± 8.7 years) using [C‐11]Pittsburgh compound B (PiB) PET imaging. DS‐specific PiB templates were created for Aβ carrying capacity ( K ) and non‐specific binding ( NS ). Results: The highest values of Aβ carrying capacity were found in the striatum and precuneus. Longitudinal changes in AβL displayed less variability when compared to SUVrs. Discussion: These results highlight the utility of AβL for characterizing Aβ deposition in DS. Rates of Aβ accumulation in DS were found to be similar to that observed in late‐onset Alzheimer's disease (AD; ≈3% to 4% per year), suggesting that AD progression in DS is of earlier onset but not accelerated.